Arabic Loanwords in Selṭi - Leslau, Wolf (Aethiopica, 1999)
Sǝlṭi belongs to the East Gurage group, along with Wolane and Zway. The East Gurage group is closely related to Harari. The article has the following subsections: 1. Correspondence between the Arabic and the Sǝlṭi consonants. 2. The correspondence between the Sǝlṭi and the Arabic consonants. 3. Observations on the loanwords. 4. A list of the Arabic loanwords. ATTENTION: Due to copy-right no online publication is provided.